Dietary intake of alpha-linolenic acid and low ratio of n-6:n-3 PUFA are associated with decreased exhaled NO and improved asthma control - Renata Barros (2011)
As recently described, adherence to the Mediterranean diet is associated with improved asthma control. However, evidence of how specific nutrients such as fatty acids and antioxidants may affect this relationship remains largely unknown. We aimed to examine the association between dietary intake of fatty acids and antioxidants and asthma control. A cross-sectional study was developed in 174 asthmatics, mean age of 40 (so 15) years. Dietary intake was obtained by a FFQ, and nutritional content was calculated using Food Processor Plus (TM) software (ESHA Research, Inc., Salem, OR, USA). Good asthma control was defined by the combination of forced expiratory volume during the first second, exhaled NO (eNO) and Asthma Control Questionnaire (ACQ) score (control: forced expiratory volume in the first second >= 80%; eNO <= 35 ppb; ACQ <1.0, scale 0-6 score). Multiple linear and logistic regression models were performed to analyse the associations between nutrients and asthma outcomes, adjusting for confounders. A high n-6:n-3 PUFA ratio predicted high eNO, whereas high intakes of n-3 PUFA, alpha-linolenic acid (ALA) and SFA were associated with low eNO. Odds for controlled asthma improved along with an increased intake of n-3 PUFA (OR 0.14, 95% Cl 0.04, 0.45; P for trend=0.001), SFA (OR 0.36, 95% CI 0.13, 0.97; P for trend=0.047) and ALA (OR 0.18, 95% CI 0.06, 0.58; P for trend=0.005). A high n-6:n-3 PUFA ratio increased the odds for uncontrolled asthma (OR 3.69, 95% CI 1.37, 9.94; P for trend=0.009), after adjusting for energy intake, sex, age, education and use of inhaled corticosteroids. Higher intakes of n-3 PUFA, ALA and SFA were associated with good asthma control, while the risk for uncontrolled asthma increased with a higher n-6:n-3 PUFA ratio. The present results introduce a protective effect of ALA in asthma control, independent of marine n-3 fatty acids, and provide a rationale to dietary intervention studies in asthma.